Years of Blindness Lead to “Visualize” Space Through Time - Amadeo, Maria Bianca; Campus, Claudio; Gori, Monica (Frontiers in Neuroscience, 2020)
Spatial representation has been widely studied in early blindness, whereas research about late blindness is still limited. We recently demonstrated that the early (50–90 ms) event-related potential (ERP) response observed in sighted people during a spatial bisection task, is altered in early blind people and is influenced by the amount of time spent without vision in late blind individuals. Specifically, in late blind people a shorter period of blindness is associated with strong contralateral activation in occipital cortex and good performance during the spatial task - similar to that of sighted people. In contrast, non-lateralized occipital activation and lower performance characterize late blind individuals who have experienced a longer period of blindness - similar to that of early blind people. However, the same early occipital response activated in sighted individuals by spatial cues has been found to be activated by temporal cues in early blind individuals. Here, we investigate whether a similar temporal attraction can explain the neural and behavioral changes observed after many years of blindness in late blind people. An EEG recording was taken during a spatial bisection task where coherent and conflicting spatio-temporal information was presented. In participants with long blindness duration, the early recruitment of both visual and auditory areas is sensitive to temporal instead of spatial coordinates. These findings highlight some limits of neuroplasticity. Perceptual advantages from cross-sensory calibration during development seem to be subsequently lost following years of visual deprivation. This result has important implications for clinical outcomes following late blindness, highlighting the importance of timing in intervention and rehabilitation programs that activate compensatory strategies soon after sensory loss.